Immunological evaluation of young unvaccinated patients with Turner syndrome after COVID-19 - de Castro, Mateus V.; Silva, Monize V.R.; Oliveira, Luana de M.; Gozzi-Silva, Sarah C.; Naslavsky, Michel S.; Scliar, Marilia O.; Magalhães, Monize L.; da Rocha, Katia M.; Nunes, Kelly; Castelli, Erick C. [UNESP]; Magawa, Jhosiene Y.; Santos, Keity S.; et al. (Elsevier, 2023)
Objectives: The X-chromosome contains the largest number of immune-related genes, which play a major role in COVID-19 symptomatology and susceptibility. Here, we had a unique opportunity to investigate, for the first time, COVID-19 outcomes in six unvaccinated young Brazilian patients with Turner syndrome (TS; 45, X0), including one case of critical illness in a child aged 10 years, to evaluate their immune response according to their genetic profile. Methods: A serological analysis of humoral immune response against SARS-CoV-2, phenotypic characterization of antiviral responses in peripheral blood mononuclear cells after stimuli, and the production of cytotoxic cytokines of T lymphocytes and natural killer cells were performed in blood samples collected from the patients with TS during the convalescence period. Whole exome sequencing was also performed. Results: Our volunteers with TS showed a delayed or insufficient humoral immune response to SARS-CoV-2 (particularly immunoglobulin G) and a decrease in interferon-γ production by cluster of differentiation (CD)4+ and CD8+ T lymphocytes after stimulation with toll-like receptors 7/8 agonists. In contrast, we observed a higher cytotoxic activity in the volunteers with TS than the volunteers without TS after phorbol myristate acetate/ionomycin stimulation, particularly granzyme B and perforin by CD8+ and natural killer cells. Interestingly, two volunteers with TS carry rare genetic variants in genes that regulate type I and III interferon immunity. Conclusion: Following previous reports in the literature for other conditions, our data showed that patients with TS may have an impaired immune response against SARS-CoV-2. Furthermore, other medical conditions associated with TS could make them more vulnerable to COVID-19.
Keywords: COVID-19; SARS-CoV-2; Turner syndrome; X-chromosome